HL-1167: Efficacy of Autologous Stem Cell Transplantation for Hodgkin Lymphoma Involving Hight-Dose Chemotherapy: A Systematic Review and Meta-Analysis - Prashanth, Disha; Kapoor, Tanay; Bellur, Vinay C.; Prasad, Ananya; Bhavanam, Sravani; Chitlur, Hitha; Gold-Olufadi, Shakirat; Saparov, Dosbai; Kriplani, Kushal (Clinical lymphoma, myeloma and leukemia, 2025)
The effectiveness of high-dose chemotherapy or radiation in treating various cancers is limited due to the myelosuppressive effect at high doses, leading to dose-limiting bone marrow suppression. Autologous stem cell transplantation (ASCT) as adjunctive therapy plays a key role in treatment protocols involving high-dose chemotherapy (HDC), with promising overall survival and progression-free survival among patients with Hodgkin lymphoma. ASCT is also the standard of care for patients experiencing relapse and is curative in 50% of these cases. This meta-analysis aims to highlight the efficacy of ASCT/HDC therapy. A systematic search was conducted using PubMed, Google Scholar, and Scopus. A Boolean expression was constructed to search the databases, and articles involving the administration of ASCT with HDC with reported overall survival (OS) and progression-free survival (PFS) were retrieved. The statistical analysis was conducted in R-Studio. The outcomes analyzed were the pooled OS and PFS proportions to highlight the efficacy of ASCT/HDC in Hodgkin lymphoma. The data were analyzed using the Meta, Metadata, and Metafor packages of R studio. The proportion of the population was assessed using the random intercept logistic regression model. An I2 test evaluated the heterogeneity of the studies. A total of eight studies involving 1261 subjects were included in the meta-analysis. The rates of OS and PFS for a minimum of 2 years following HDC/ASCT were used as outcomes to assess the therapeutic value of HDC/ASCT. The pooled proportion of OS 2 years after HDC/ASCT was estimated to be 0.7328 (95% CI 0.5417–0.8642, I2 = 96.9% [95.5–97.9%], H= 5.70 [4.70–6.90], P < 0.001), and the pooled proportion of PFS was estimated to be 0.5716 (95% CI 0.4376–0.6959, I2 = 80.9% [61.5–90.6%], H= 2.29 [1.61–3.26], P < 0.001). ASCT is associated with a promising OS rate in patients with Hodgkin lymphoma. It also results in more than half of patients achieving PFS of at least 2 years. Thus, in patients experiencing relapsing or refractory Hodgkin lymphoma, ASCT proves to be a promising novel therapeutic option with optimistic outcomes.